Constituent Postponement in Biblical Hebrew Verse - Redd, John Scott (Wiesbaden Harrassowitz Verlag, 2014)
Cover; Title Page; Copyright; Table of Contents; List of Tables; List of Abbreviations; Linguistic Abbreviations; Preface; Body; 1 Introduction; The Present Interest; Poetry and Prose; Formal Defamiliarization; 2 Classical Biblical Hebrew Prose; Distinct Phases in Biblical Hebrew; Word Order in Classical Biblical Hebrew; 3 Preverbal Constituents in BH Prose; Introduction; Two Preverbal Constituents in BH Prose; Previous Analysis: Word Order Studies; Word Order Studies in Verse; Rosenbaum (1997); Gross (1996, 2001); Lunn (2006); Complements and Adjuncts; Corpus; 4 Verbal Postponement.
IntroductionCriteria; Preposed Constituent; Adverbs; Discourse Markers; Constituents of the Clause; Cases of V-Postponement in the Sample; Divine Name; A- and B-lines; Syntactic Tropes: Matching and Syntactic Dependency; Coordination; Coordinated Lines ; Uncoordinated Lines; V-Postponement Overview-Categorial Patterns; V-Postponement Overview-Grammatical Role Patterns; Complementation/Adjunction; Complementation/Adjunction in First Position; Complementation/Adjunction in Second Position; Canonical Context; Canonical Context Breakdown; Conclusion; 5 Subject- and Object-Postponement.
IntroductionPostverbal Word Order in CBH; S-Postponement; Factors in S-Postponement; Varieties of S-Postponement; Excursus: The Pragmatics of S-Postponement; O-Postponement; Factors in O-Postponement; Complements and Adjuncts in O-Postponement; Canonical Context S- and O-Postponement; Canonical Context Breakdown; Conclusions to S- and O-Postponement; 6 Conclusion; Bibliography; Index; Abstract.
What are the elements of Biblical Hebrew (BH) verse? Much headway has been made in terms of describing the features and devices that find expression in BH verse, but there is more to be said particularly about the distinction between verse and prose. Though BH verse is governed by a terse poetic line, it also exhibits "relaxed" syntactic structure, wherein certain syntactic constructions that would be unviable in prose are acceptable. One such construction is the occurrence of constituent postponement in the verbal clause, such as postverbal subject- and object-postponement as well as verb-pos
Keywords: Bible -- Language, style; Hebrew poetry, Biblical -- History and criticism; Hebrew prose literature -- History and criticism; Hebrew language -- Verb phrase; Hebrew language -- Word order; Hebrew language -- Clauses; Bible; Hebrew language ; Clauses; Hebrew language ; Verb phrase; Hebrew language ; Word order; Hebrew poetry, Biblical; Hebrew prose literature; LITERARY CRITICISM / Ancient & Classical; Criticism, interpretation, etc; Language and languages - Style; Poésie hébraïque biblique - Histoire et critique; Prose hébraïque - Histoire et critique